RECONSTRUCTING THE STATUS OF CONSTITUTIONAL COURT RESEARCHERS: MEREKONSTRUKSI STATUS PENELITI MAHKAMAH KONSTITUSIONAL - Barus, Sonia Ivana; Saifulloh, Putra Perdana Ahmad; Amancik; Nikenuna, Syifa (Pusat Studi Konstitusi dan Perundang-undangan, 2026)
Researchers at state institutions were forced to leave their positions, including those at the Constitutional Court. Researchers then lose the opportunity to hold the title of research professor. These researchers were also given a new duty, which was to help courts and give Constitutional Justices substantial support. The predicate “assistance